Shifting from Technology Transfer to Learning Facilitation in Extension: An Empirical Analysis - Ashley A Carroll; Kevan W. Lamm; Kristi Carpenter; D Barry Croom; Nicholas E. Fuhrman PhD; Masoud Yazdanpanah (Journal of International Agricultural and Extension Education, 2025)
Extension has traditionally been recognized as a leader in delivering research-based information to meet the needs of local stakeholders and their communities, often through a linear model commonly referred to as the transfer of technology. For many reasons, linear extension has been criticized for its top-down approach, which focuses on the transfer of technology while neglecting client involvement and participation. Critics have called for reforms in extension systems globally, particularly in developing nations, to make them more stakeholder-driven and accountable to stakeholders in general. This study provides an empirical examination of the primary facilitation needs associated with extension professionals using the Borich approach. An extension leadership team (n = 19) located in the United States served as the panel of experts for the process. The group identified both the importance and perceived skill level of extension professionals in their state on 22 facilitation competencies. A mean weighted discrepancy score (MWDS) was calculated to identify areas of developmental need. Communication and interpersonal skills were identified as most important. Helping design/adapt a program to meet local needs was identified as the competency with the highest existing skill level. Based on the MWDS analysis the greatest facilitation developmental needs include stakeholder engagement and training, mentoring, and coaching skills. Transitioning from linear, top-down education and technology transfer to facilitative and stakeholder engaged practice will require fundamental shifts in extension. This research provides a foundation for such efforts and a set of empirical findings to inform future efforts.
Keywords: Extension; Facilitation; Borich